Potentially effective method for fetal gender determination by noninvasive prenatal testing for X‐linked disease. (6th July 2018) - Noda, Yoshiteru; Kato, Takema; Kato, Asuka; Nishizawa, Haruki; Miyazaki, Jun; Ito, Mayuko; Terasawa, Sumire; Sekiya, Takao; Fujii, Takuma; Kurahashi, Hiroki
Abstract : Examination of maternal plasma cell‐free DNA (cfDNA) for noninvasive prenatal testing for fetal trisomy is a highly effective method for pregnant women at high risk. This can be also applied to fetal gender determination in female carriers of severe X‐linked disease. Polymerase chain reaction (PCR) analysis is a relatively simpler and less expensive method of detecting Y chromosome‐specific repeats (Y‐specific PCR; YSP), but is limited by the risk of false‐negative results. To address this, we have developed a combined strategy incorporating YSP and an estimation of the fetal DNA fraction. Multiplex PCR for 30 single nucleotide polymorphism (SNP) loci selected by high heterozygosity enables the robust detection of the fetal DNA fraction in cfDNA. The cfDNA sample is first subjected to YSP. When the YSP result is positive, the fetus is male and invasive testing for an X‐linked mutation is then required. When the YSP result is negative, the cfDNA sample is analyzed using multiplex PCR. If fetal DNA is then found in the cfDNA, invasive testing is not then required. If the multiplex PCR analysis of cfDNA is negative for fetal DNA, the fetal gender cannot be determined and invasive testing is still required. Our technique provides a potentially effective procedure that can help to avoid unnecessary invasive prenatal testing in some female carriers of severe X‐linked disease.